2018
DOI: 10.1371/journal.pbio.2003453
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamines alter the intrinsic variability of cortical population activity and perception

Abstract: The ascending modulatory systems of the brain stem are powerful regulators of global brain state. Disturbances of these systems are implicated in several major neuropsychiatric disorders. Yet, how these systems interact with specific neural computations in the cerebral cortex to shape perception, cognition, and behavior remains poorly understood. Here, we probed into the effect of two such systems, the catecholaminergic (dopaminergic and noradrenergic) and cholinergic systems, on an important aspect of cortica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
65
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 119 publications
12
65
4
Order By: Relevance
“…With the additionally demonstrated excellent test-retest reliability of obtained CBF to receptor density profiles, these findings further strengthen the value of CBF as a promising tool for drug development and disease evaluation. Our findings and other recent research demonstrate that a combination of pharmacological modulations with neurophysiological read-outs can provide novel insight into specific mechanisms of brain function 50 , 51 . Overall, this research shows that the combination of both techniques may provide a unique cross-species translational approach for studying local and remote neurophysiological and neurometabolic effects associated with modulation of specific neurotransmitter systems.…”
Section: Discussionsupporting
confidence: 66%
“…With the additionally demonstrated excellent test-retest reliability of obtained CBF to receptor density profiles, these findings further strengthen the value of CBF as a promising tool for drug development and disease evaluation. Our findings and other recent research demonstrate that a combination of pharmacological modulations with neurophysiological read-outs can provide novel insight into specific mechanisms of brain function 50 , 51 . Overall, this research shows that the combination of both techniques may provide a unique cross-species translational approach for studying local and remote neurophysiological and neurometabolic effects associated with modulation of specific neurotransmitter systems.…”
Section: Discussionsupporting
confidence: 66%
“…This was supported, in the same study, by pharmacological modulation showing that potentiation of the catecholaminergic system leads to increased LRTC both during eyes-open rest and during a structure-from-motion task. Surprisingly, Pfeffer et al ( 2018 ) reported an increase in the number of perceptual switches when pharmacologically increasing LRTC of alpha oscillations in occipital and parietal regions, which is unexpected in view of the negative association that we report here for the within-subject relationship between LRTC and perceptual switches. It is likely that the pharmacological manipulation in Pfeffer et al ( 2018 ) affects aspects of neuronal dynamics other than LRTC in a different manner from our study, resulting in the observed discrepancy.…”
Section: Discussioncontrasting
confidence: 68%
“…Surprisingly, Pfeffer et al ( 2018 ) reported an increase in the number of perceptual switches when pharmacologically increasing LRTC of alpha oscillations in occipital and parietal regions, which is unexpected in view of the negative association that we report here for the within-subject relationship between LRTC and perceptual switches. It is likely that the pharmacological manipulation in Pfeffer et al ( 2018 ) affects aspects of neuronal dynamics other than LRTC in a different manner from our study, resulting in the observed discrepancy. It is known that activity in the locus-coeruleus norepinephrine system is related to the level of arousal (Rajkowski et al, 1994 ; Aston-Jones et al, 2007 ).…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations